Understanding of Special Teachers in Teaching Children with Special Needs at Inclusive Schools - Djadja Rahardja (Department of Special Education, 2017)
This study aims to obtain an objective picture of understanding of special teachers of the concept of children with special needs, teaching, and the concept of inclusive education. This research uses descriptive method with data collection in the form of a questionnaire. Based on research results, there are three findings: 1) understanding of special teachers on the concept of children with special needs are at the translational level, while for the classification and their impact are not yet at the translation level, 2) understanding of the special teachers on planning, implementation, and evaluation of teaching children with special needs in inclusive settings are not already on the translational level; and 3) understanding of the special teachers on concepts, philosophies and policies related to inclusive education are not at the level of translation.